P3HB from CH4 using methanotrophs: aspects of bioreactor, fermentation process and modelling for cost-effective biopolymer production - Safaeian, Parya; Yazdian, Fatemeh; Khosravi-Darani, Kianoush; Rashedi, Hamid; Lackner, Maximilian (Frontiers in Bioengineering and Biotechnology, 2023)
Poly(3-hydroxybutyrate) (PHB) is an important and promising biopolymer, which is degradable also in the marine environment. Compared to its fossil counterparts, PHB has comparatively high production costs, which limit the material’s possible applications and proliferation. In this work, a novel way to produce PHB sustainably and cost-effectively was studied. Biosynthesis of PHB by methanotrophs from methane (CH4) and selection of the best culture were carried out. Clearly, for every biopolymer, the carbon source substrate is an important cost driver, and often starch or sugar are used for bioplastics manufacturing, where an ethical concern over conflicting feed/food use may arise. CH4 can be converted into PHB by aerobic methanotrophs, and it is accessible through natural gas, biomass gasification, biogas and landfill gas, for instance. Natural gas as a cheap carbon source can be of particular interest for oil-rich countries, and also bring environmental advantages when e.g. flaring is avoided. The authors discuss several types of bioreactors because the first step in PHB production is biomass growth. Monitoring the operation design by silico simulations instead of applying a wide range of lab-scale experiments in order to optimize several parameters can be done to save time and substrates. In order to determine the role of flow parameters, mathematical methods are accessible, complementing experiments for nutrients and effective feeding strategies as shown in this paper. PHB from methane was found to be a promising route of production.